Implementation of Hazard Analysis and Critical Control Point (HACCP) in Cu’s Chicken Crispy Production Process - A.R. Yelvia Sunarti; Moch Akbar Munin Putra; Moh Nur Fuadzi; Erwan Adi Saputro; Ika Nawang Puspitawati (Future Science, 2022)
Food safety issues are still an important issue in the food sector in Indonesia and need special attention in food control programs. Therefore, it is necessary to improve the quality and safety of the products produced by developing a food safety assurance system in the form of a Hazard Analysis and Critical Control Point (HACCP). HACCP is a food safety assurance system in the form of a systematic approach to identifying hazards and put in place control systems to prevent them. One of the important reasons for implementing the HACCP system in the food industry is because the ingredients used during the production process have the possibility of contamination that can harm consumers. Cu's Chicken Crispy is a small industry that produces food. His party wants to implement a Hazard Analysis Critical Control Point (HACCP) management system to improve product quality assurance. This study aims to identify hazards related to the production aspects (raw materials, packaging, and processes) of Cu’s Chicken Crispy and determine the CCP related to the production of Cu’s Chicken Crispy. This study conducted a direct interview with the owner and made a direct visit to Mrs. Cu's food stall. In this study, it was found that there is a significant potential danger to chicken meat raw materials. At the stage of the production process that falls into the category of salting, draining and packaging refer to CCP.